Who Pays the Most for Water? Alternative Providers and Service Costs in Niger - Bardasi, Elena; Wodon, Quentin (2012)
Despite water being subsidized in most developing countries, poorer households end up paying more per unit of consumption because they are generally not connected to the network and, as a result, are forced to buy water from public fountains or street vendors at a higher price. In this note, we use a unique survey of Niamey households including information on water consumption and expenditure from different sources to estimate unit costs of service provision for water, looking at differences in costs according to both service provider and household poverty status. Our results indicate that the poor pay much higher unit prices for the water they consume than better off households who are connected to the network.